2011
DOI: 10.1136/jme.2010.039057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in granted and refused requests for euthanasia and assisted suicide: a systematic review

Abstract: It is unclear whether depression increases the probability of making a request for euthanasia/PAS, but in the Netherlands most requests in depressed patients are rejected, leaving a depression rate in cases that is similar to the surrounding population. Less evidence is available elsewhere, but some level of depression has been identified in patients undergoing euthanasia/PAS in all the countries studied. Whether the presence of depression is ever compatible with an ethical decision on euthanasia/PAS is discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 50 publications
0
26
0
4
Order By: Relevance
“…Levene and Parker37 reviewed 21 studies pertaining to depression among people who have made explicit requests for euthanasia or assisted suicide. They concluded that in The Netherlands and the US State of Oregon, which permit these practices in some circumstances, 8–47% of patients who make such requests have high levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Levene and Parker37 reviewed 21 studies pertaining to depression among people who have made explicit requests for euthanasia or assisted suicide. They concluded that in The Netherlands and the US State of Oregon, which permit these practices in some circumstances, 8–47% of patients who make such requests have high levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether depression increases the likelihood that a patient will request PAS or euthanasia [32], or interferes with their competence to do so. Assessing competence to make such decisions presents clinicians with new challenges [33], and little research has been done to show that assessment instruments validly reflect competence for those decisions.…”
Section: Depression and Autonomymentioning
confidence: 99%
“…243 In 2005, there were alleged to be three cases where individuals with mental disorder were prescribed lethal medication, although in two of these cases the claims regarding the presence of mental disorder are likely to be unreliable, since the diagnoses appeared to rely on press reports and were refuted by the examining clinicians.244 A recent systematic review of the prevalence of depression in granted and refused requests for euthanasia and assisted suicide identified a single high quality study (cross sectional survey) that had been conducted in Oregon. 245 Of the patients making a request for physician assisted suicide, 15/58 (26 per cent) met the criteria for depression, with 3/18 (17 per cent) being prescribed lethal medication.246 It is not known whether the depressive disorder influenced the judgment of the three individuals who received physician assisted suicide, and therefore whether the assistance was lawful under the DWDA.247 However, Ôthe majority of patients requesting physician assisted suicide did not rank depression as a motivating factor in their requestÕ.248…”
Section: Request Capacitymentioning
confidence: 99%
“…347 (In such cases, provided that the individual retains capacity, the authors of the systematic review conclude that Ôit is possible for euthanasia/PAS [physician assisted suicide] to be a valid choice despite the presence of depressionÕ. 348 ) In the Netherlands, depression is significantly less prevalent in granted requests than in refused requests, and severe depression is not significantly present in requests generally.…”
Section: Condition And/or Experience Of Sufferingmentioning
confidence: 99%